Interaction of Cannabis Use and Aging: From Molecule to Mind. Issue 1 (2nd January 2020) - Yoo, Hye Bin; DiMuzio, Jennifer; Filbey, Francesca M.
Abstract: Given the aging Baby Boomer generation, changes in cannabis legislation, and the growing acknowledgment of cannabis for its therapeutic potential, it is predicted that cannabis use in the older population will escalate. It is, therefore, important to determine the interaction between the effects of cannabis and aging. The aim of this report is to describe the link between cannabis use and the aging brain. Our review of the literature found few and inconsistent empirical studies that directly address the impact of cannabis use on the aging brain. However, research focused on long-term cannabis use points toward cumulative effects on multimodal systems in the brain that are similarly affected during aging. Specifically, the effects of cannabis and aging converge on overlapping networks in the endocannabinoid, opioid, and dopamine systems that may affect functional decline particularly in the hippocampus and prefrontal cortex, which are critical areas for memory and executive functioning. To conclude, despite the limited current knowledge on the potential interactive effects between cannabis and aging, evidence from the literature suggests that cannabis and aging effects are concurrently present across several neurotransmitter systems. There is a great need for future research to directly test the interactions between cannabis and aging.